2015
DOI: 10.1080/15402002.2015.1018386
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Restless Legs Syndrome in Adult ADHD and Its Subtypes

Abstract: In this observational cross-sectional study, 49 subjects were assessed for sleep disorders and for ADHD symptoms. Thirty-six received an ADHD diagnosis (29: combined type (ADHD-C); 7: inattentive type). An RLS and RLS symptoms prevalence of 34.5% was found, with a higher prevalence rate in the ADHD-C subgroup, although not significantly (p = 0.066). RLS symptoms were correlated with particularly hyperactivity-impulsivity (ρ = 0.742; p: 0.000). ADHD patients with positive RLS scores reported higher scores on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Prevalence of suspected SRMD was high in patients with affective disorder and type B personality disorders, which could be related to the RLS stimulating effects of many antidepressants, and atypical antipsychotics (Patatanian & Claborn, 2018; (Rottach et al, 2008; Wichniak et al, 2017). Additionally, in agreement with literature (Snitselaar et al, 2016), SRMD was commonly found in those with ADHD. One may speculate whether either the effects of stimulants prescribed for ADHD or overlap in aetiology between RLS and ADHD such as dopaminergic dysregulation could be partially responsible for this trend (Wajszilber et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Prevalence of suspected SRMD was high in patients with affective disorder and type B personality disorders, which could be related to the RLS stimulating effects of many antidepressants, and atypical antipsychotics (Patatanian & Claborn, 2018; (Rottach et al, 2008; Wichniak et al, 2017). Additionally, in agreement with literature (Snitselaar et al, 2016), SRMD was commonly found in those with ADHD. One may speculate whether either the effects of stimulants prescribed for ADHD or overlap in aetiology between RLS and ADHD such as dopaminergic dysregulation could be partially responsible for this trend (Wajszilber et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Although comparison of these prevalences with prevalences from other research is difficult due to variability in the studied samples and methodology, our prevalences of an extreme evening chronotype [30] and ID [51] were quite consistent with those from previous studies. Our prevalences of probable OSAS [52,53], RLS [19,54], ID with predominant DIS [10,30,33,55] and DMS [33,56] were within the range of other studies. Regarding PLMD [56], narcolepsy [57], ID with predominant EMA [33], and sleep 6 h [58], we observed lower prevalence rates as compared to other studies.…”
Section: Discussionsupporting
confidence: 83%
“…Die hohe Zahl der Patienten mit Depressionen ist auch dem Umstand geschuldet, dass wir auf der von uns untersuchten Station primär Patienten mit affektiven Störungen aufnahmen. Die Patienten mit ADHS litten häufig an bipolaren Störungen, paranoiden Schizophrenien, Angststörungen, emotional-instabilen und zwanghaften Persönlichkeitsstörungen, Teilleistungsstörungen, Nikotinabhängigkeit, Substanzabhängigkeiten, Substanzmissbräuchen, Restless-legs Syndromen, Essstörungen und Adipositas, was auch andere Autoren beschrieben [2,5,7,10,11,16,17,18,19,20,21,22,23,24,25,26,27]. Bei der schizoaffektiven Störung, Zwangsstörung und organischen Persönlichkeitsstörung fanden sich keine Häufungen.…”
Section: Diskussionunclassified